Plasma-assisted synthesis of non-stoichiometric nanoceria powder from cerium carbonate hydroxide (CeCO3OH) - Lan, Yuan-Pei; Sohn, Hong Yong; Liu, Qingcai (Metallurgical and Materials Engineering, 2017)
Highly non-stoichiometric nanoceria was synthesized for the first time by thermal plasma from the precursor cerium carbonate hydroxide. The particle size was approximately 60 nm according to measurement by TEM. The nanoceria synthesized with 25 kW plasma power with argon as the carrier gas had the largest concentration of oxygen vacancies, follow by that produced with 20 kW with hydrogen as the carrier gas. XRD results indicated that the CeO1.66 phase was present with mostly non-stoichiometric ceria CeO2-x in these two products. SEM and TEM images showed that most of the particles were of irregular shape, while some triangular particles were also present. Raman spectra revealed that the F2g mode of synthesized nanoceria powders had a remarkable downshift of 7.9 - 10.5 cm-1 relative to the peak for single crystal ceria located at 466.0 cm-1. The Raman downshift was explained by the increase in ionic radius upon Ce4+ reduction to Ce3+. XPS results indicated that the Ce3+ content on the surface of the synthesized nanoceria was in the range of 15-30 %, depending on the plasma power and carrier gas composition. Both the Raman and XPS spectra showed numerous oxygen vacancies in the nanoceria. The results of this work indicated that the oxygen vacancy formation occurred when the CeO2 formed from the oxidation of cerium carbonate hydroxide was reduced by the hydrogen as well as the high temperature of the plasma. This investigation has verified that plasma treatment provides a promising method for the synthesis of nanoceria powder with high oxygen vacancies.